1972
DOI: 10.1677/joe.0.0530223
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prolactin in the Regulation of Testis Function: The Synergistic Effects of Prolactin and Luteinizing Hormone on the Incorporation of [1-14c]acetate Into Testosterone and Cholesterol by Testes From Hypophysectomized Rats in Vitro

Abstract: Hypophysectomized adult male rats were treated twice daily for 3\ m=1/ 2\ days with 0\m=.\9% NaCl solution, 200 \g=m\g ovine prolactin, 5 \g=m\g ovine luteinizing hormone (LH), or 200 \g=m\gprolactin +5 \g=m\gLH, starting 18 days after the operation. Minced testes from these animals were incubated in Krebs\p=m-\Ringer bicarbonate buffer containing [1-14C]acetate for 3 h at 37 \s=deg\C.The conversion of acetate into testosterone was calculated. It was not changed by prolactin treatment, was increased by LH (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

1973
1973
1998
1998

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…Hafiez et al (16) showed that PRL administration to hypophysectomized male rats caused a slight rise in plasma testosterone, and LH + PRL produced testosterone levels about 3-fold higher than did LH alone. Also in these rats, PRL acted synergistically with LH to promote 14 Cacetate incorporation into testosterone in testicular tissue in vitro (36). These authors (16) summarized their earlier studies, in which PRL acted synergistically with LH to restore spermatogenesis (an androgendependent function) in hypophysectomized hereditary dwarf mice, and PRL increased testicular 3/3-hydroxysteroid dehydrogenase activity and promoted testicular accumulation of esterified cholesterol in these mice.…”
Section: Discussionmentioning
confidence: 94%
“…Hafiez et al (16) showed that PRL administration to hypophysectomized male rats caused a slight rise in plasma testosterone, and LH + PRL produced testosterone levels about 3-fold higher than did LH alone. Also in these rats, PRL acted synergistically with LH to promote 14 Cacetate incorporation into testosterone in testicular tissue in vitro (36). These authors (16) summarized their earlier studies, in which PRL acted synergistically with LH to restore spermatogenesis (an androgendependent function) in hypophysectomized hereditary dwarf mice, and PRL increased testicular 3/3-hydroxysteroid dehydrogenase activity and promoted testicular accumulation of esterified cholesterol in these mice.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, it has been recently demonstrated that PRL receptors are present in all stages of the cycle of the seminiferous epithelium, the surface of Leydig and Sertoli cells, all phases of spermatogonia and spermatocytes in male rats (23), suggesting that PRL plays a pivotal role in the development of spermatogenesis. In addition, several older studies on animals demonstrated that normal serum PRL levels are required for a normal testicular function and growth of accessory sex organs, since PRL acts synergistically with LH and testosterone (24,25) and it regulates the levels of the testosterone precursors for conversion under the in¯uence of LH (25). On the other hand, hyperprolactinemia suppressed LH pulse frequency in castrated male rats (26) and decreased testosterone levels by inhibiting gonadotropin-releasing hormone and, consequently, gonadotropin secretion in men (27).…”
Section: Discussionmentioning
confidence: 99%
“…PRL has emerged as the pituitary hormone most likely to account for prostate gland evolution [35], The proliferative effects of PRL are closely associated with androgens. Indeed, PRL can act indirectly on the prostate by altering androgen biosynthe sis at the testis [ 14], or directly in synergism with testoster one by an 'increase in androgen nuclear receptors' [10].…”
Section: Discussionmentioning
confidence: 99%